Promoting ECVET to practitioners : the NetECVET network - Drews, Sibilla [Verfasser]; Curth, Anette [Verfasser] (My University, 2012)
This article describes the NetECVET network, which promotes ECVET in the context of transnational mobility. The NetECVET network consists of National Agencies from 14 European countries and "supports the implementation process in the Member States through a bottom-up approach. It addresses VET providers and actors in VET and supports and guides them in the application of ECVET. (Extract, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; L 4.2.4 Expertennetzwerke / Wissensplattformen; I 2.2 Europa; Europäisches Leistungspunktesystem; Netzwerk; Europa